Evaluation of the physicochemical properties and the performance of the three generations of biodiesel through the transesterification process: a review (Research, Society and Development, 2022)
With the search for alternative sources for the production of biofuels, biodiesel emerges as a favorite substitute to reduce the use of fossil fuels. Biodiesel production is so diverse that it has been categorized into three generations. The first includes food and non-edible crops, the second generation is biodiesel originated from organic residues and residual food substrates and the third generation is composed of microorganisms, such as yeast fungi, among others. The present work aims to present a literature review concerning the physicochemical properties of the three generations of biodiesel produced by the transesterification process. With the information collected, it was found that the raw materials of each generation have different characteristics and compositions. In general, the transesterification process showed efficiency according to the conversion percentages and by adapting the oils into biofuels according to the specifications. Among the three generations, vegetable oils showed better performance, except for castor oil biodiesel. Analyzing the possible replacement of diesel, the best biomasses were Portulaca (weed), hat napoleão and Jatropha, due to the characteristics of having low specific mass, adequate viscosity for the application, higher cetane number, high flash point, low temperature for the cloud point and high conversion. They are still characterized by being inedible, avoiding competitiveness with the food sector. Third-generation biodiesel did not perform well and some residual fat oil research has shown great promise.